Monarchische Herrschaft im Altertum - Rebenich, Stefan; Wienand, Johannes (Schriften des Historischen Kollegs, 2017)
"Monarchical rule was omnipresent in the ancient world, but until now, there has been no comparative study of the phenomenon across epochs and cultures. The volume fills this gap, examining autarchy in the ancient Near East, across Greco-Roman antiquity, and up to the early Middle Ages. It includes a comparison with ancient China, and an essay from the perspective of reception history"--Provided by publisher
Literaturangaben
"Die Beiträge zu dem vorliegenden Band sind aus einem Kolloquium über "Monarchische Herrschaft im Altertum" hervorgegangen, das vom 23. bis 25. Januar 2014 am Historischen Kolleg in München stattfand" (Dank)
Keywords: Konferenzschrift -- 2014 -- München; Monarchie; Altertum; Monokratie